Voices of learning: Investigating the impact of Nasheed (Hymns) on language acquisition among international students in Jordan - Almubasher, Zakaria Mahmoud; Abu-Rahme, Mohammed O; Mustafa Kh. Dabash, Almu'tasembellah; AL-Salman, Ahmad Mohammad (Research Journal in Advanced Humanities, 2026)
This study aimed to study the effect of nasheed in enhancing language acquisition among international students at the Applied Science Private University in Jordan. The semi-experimental approach was used, and the study members consisted of 40 foreign students who did not speak Arabic at the Applied Science Private University. The sample was divided into two parts: an experimental group (20 students) and a control group (20 students). The experimental group studied the use of chants to develop Language skills, especially oral expression, which are important for communicating with the outside community, while the control group was studied using traditional methods. Pre- and post-tests were applied to the study samples. The achievement test was prepared as a tool, and the data was analysed statistically. The results showed that there were statistically significant differences in favour of the experimental group, which confirms the effectiveness of using songs in developing Arabic language skills among non-native Arabic-speaking foreigners. I recommend activating the role of nasheed in the educational process because of its positive impact, which leads to improving the performance of students in general.